Peningkatan Kemampuan Literasi Digital Guru Melalui Pelatihan Aplikasi Assemblr Edu di SD Negeri Rumpet - maulida maulida; Hafnati Rahmatan; Mawarni Saputri; Fitrah Asma Ulhusna (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
Abstract: Digital literacy skills are one of the skills that must be possessed by a teacher. The development of technology and also various artificial intelligence applications are a challenge for the pedagogical skills of teachers, where teachers are required to be able to master these various applications. The Ministry of Education and Culture has also supported the improvement of technology application skills for teachers by providing premium applications through teacher affiliate email accounts. This community service activity aims to provide training to teachers related to the Assemblr Edu application at Rumpet Public Elementary School. Method: This community service activity will use 5 stages of activities, namely Socialization, Training, Technology Application, Mentoring, and Evaluation. The sample in this community service activity is 12 teachers. To assess improvements in teachers' digital literacy skills, data will be collected on teachers' initial and final abilities. Results: The improvement of teachers' digital literacy skills at Rumpet Public Elementary School has increased, as seen from the initial ability of teachers before the activity by 58% and after the activity to 86%, from a total of 12 teachers. The Esemblr Edu application training provides additional digital literacy knowledge for teachers at Rumpet Public Elementary School.